FV 14. Longitudinal recordings of eye movements confirm the model of sequential oculomotor alterations in amyotrophic lateral sclerosis consistent with the neuropathological staging scheme. Issue 9 (September 2016) - Gorges, M.; Müller, H.-P.; Lulé, D.; Tredici, K. Del; Keller, J.; Ludolph, A.C.; Kassubek, J.; Pinkhardt, E.H.
Abstract : Background: Recordings of eye movements have demonstrated that oculomotor dysfunction in patients with amyotrophic lateral sclerosis (ALS) follows a two-staged pattern (Gorges et al., 2015 ) that is consistent with the model of sequential corticofugal axonal spread of pTDP-43 pathology (Brettschneider et al., 2013 ). Eye movement abnormalities in ALS include anti- and delayed saccades errors (stage 1) as well as additional infratentorial-network associated oculomotor functions such as gaze-palsy or a cerebellar type of smooth pursuit disturbance (stage 2). We aimed to investigate whether this model can be confirmed in a larger cohort ( N = 164) and in longitudinal testing. Methods: Eye movement recordings using video-oculography (EyeSeeCam®) together with clinical (ALS-FRS) and neuropsychological scores (ECAS) from 164 ALS patients and 31 matched healthy controls were used for the analysis. Longitudinal data were available from 16 ALS patients ( ∼ 6 months after initial testing). Results: At the time of the first investigation, 60 patients presented no oculomotor deficits ('nd') compared with controls. 78 patients showed stage 1 symptoms with only executive dysfunction and 26 patients showed stage 2 pathology with additional cerebellar type of smooth pursuit and/or gaze palsy. The sequential appearance of impaired eye movement control as hypothesized byGorges et al. (2015) was confirmed by the categorization of eye movement abnormalities over time: four patients with no deficits at timepoint 1 (out of 16) developed only executive dysfunctions ( nd ⩾ stage 1) and one patient (categorized as stage 1 at timepoint 1) developed to stage 2, accompanied by a gradual worsening of executive functions. The oculomotor stages were significantly correlated (p). Conclusion: According to the cross sectional approach the model of a two-staged sequential pattern of eye movement abnormalities in ALS could be confirmed by a lager cohort. Additional preliminary longitudinal data in 16 patients showed a progression from stage 0 to 1 or from 1 to 2 respectively. Thus our data favor the hypothesis that oculomotor decline in ALS depicts the neuropathological sequential spreading of the disease instead of being the consequence of different phenotypes of ALS. Oculomotor staging may serve as a technical marker of the neuropathological disease progression in correlation to the clinical phenotype.